2008
DOI: 10.1136/jmg.2008.057943
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic CpG methylation of the KCNQ1OT1 gene during maturation of human oocytes

Abstract: This observation suggests that hyperstimulation likely recruits young follicles that are unable to acquire imprint at KvDMR1 during the course of the maturing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 40 publications
0
57
0
1
Order By: Relevance
“…In humans, using the short-term protocol on oocytes from stimulated women, H19 GOM was found in 2/10 MII oocyte pools (Borghol et al 2006) and at 3/34 DNA strands in MII oocyte pools . KCNQ1OT1 LOM was also observed in 5/23 and 2/37 DNA strands from IVM MII oocyte pools (Khoueiry et al 2008. This contrasts with short-term IVM MII oocytes that had normal SNRPN (three single oocytes), KCNQ1OT1 (four single oocytes), and MEG3 (GTL2) (three pools of two oocytes) methylation (Geuns et al 2003(Geuns et al , 2007a(Geuns et al , 2007b.…”
Section: In Vitro Oocyte Maturationmentioning
confidence: 55%
See 1 more Smart Citation
“…In humans, using the short-term protocol on oocytes from stimulated women, H19 GOM was found in 2/10 MII oocyte pools (Borghol et al 2006) and at 3/34 DNA strands in MII oocyte pools . KCNQ1OT1 LOM was also observed in 5/23 and 2/37 DNA strands from IVM MII oocyte pools (Khoueiry et al 2008. This contrasts with short-term IVM MII oocytes that had normal SNRPN (three single oocytes), KCNQ1OT1 (four single oocytes), and MEG3 (GTL2) (three pools of two oocytes) methylation (Geuns et al 2003(Geuns et al , 2007a(Geuns et al , 2007b.…”
Section: In Vitro Oocyte Maturationmentioning
confidence: 55%
“…As zona pellucidae were not removed from pooled oocytes, H19 GOM may be the result of cumulus cell contamination. Following ovarian stimulation in humans, individual MI oocytes showed PEG1 LOM (2/7 oocytes) and H19 GOM (2/3 oocytes) , and in the last study, pooled MII oocytes exhibited maternal KCNQ1OT1 LOM (2/19 strands) (Khoueiry et al 2008). With respect to the human MI oocyte study, PEG1 may still be in its acquisition phase.…”
Section: Ovarian Stimulationmentioning
confidence: 99%
“…In the female germ line, only a limited number of studies are available. In one detailed analysis, methylation at the KvDMR1 was shown to be acquired progressively during oocyte maturation and to be completed by the metaphase II stage (Khoueiry et al 2008). Similarly, the SNRPN DMR was found to be fully methylated in mature oocytes (Geuns et al 2003), suggesting a timing similar to that observed in the mouse.…”
Section: Genomic Imprinting In Germ Cellsmentioning
confidence: 90%
“…In mouse, adverse effects of superovulation on imprinted gene methylation and/or expression in oocytes, embryos, fetuses, and placentas have been described [Borghol et al, 2006;Fauque et al, 2007;Sato et al, 2007;Fortier et al, 2008;Khoueiry et al, 2008;Market-Velker et al, 2010;El Hajj et al, 2011;de Waal et al, 2012;Shi et al, 2014]. In addition, our group reported a negative impact of superovulation on the expression of mRNAs encoding the BER proteins APEX1 and POLB as well as the 5-methyl-CpG-binding domain protein MBD3 in single early mouse morula embryos.…”
mentioning
confidence: 88%